Sacred treasures of Spain sacred motets from the Golden Age of Spanish polyphony - Guerrero, Francisco 1528-1599; Ribera, Bernardino de 1520-1580; Morales, Cristóbal de 1500-1553; Robledo, Melchor 1520-1586; Esquivel Barahona, Juan de 1565-1613; Vivanco, Sebastián de 1550-1622; Victoria, Tomás Luis de 1548-1611; Lobo, Alonso 1555-1617 (Hyperion Records Limited, 2020)
The London Oratory Schola Cantorum illustrates the Golden Age with this selection of motets from sixteenth-century Spain culminating in Alonso Lobo's great funerary ode for Philip II, Versa est in luctum
Texts with English translations and program notes by Charles Cole (11 pages : portraits) inserted in container
Recorded in St Alban's Church, Holborn, London, on 16, 17 & 20 November 2017
Keywords: Motets; Choruses, Sacred (Men's voices), Unaccompanied; Sacred vocal music / Spain / 16th century; Churs sacrés (Voix d'hommes) a cappella; Musique vocale sacrée / Espagne / 16e siècle; Sacred vocal music; Spain / https://id.oclc.org/worldcat/entity/E39PBJqFTrvj6Mhw6JfTGmqJDq; 1500-1599; compact discs; Sacred music; Musique sacrée; CD